Perinatal outcomes in anemic pregnant women in public hospitals of eastern Ethiopia. Issue 3 (26th April 2022) - Debella, Adera; Eyeberu, Addis; Getachew, Tamirat; Atnafe, Genanaw; Geda, Biftu; Dheresa, Merga
Abstract: Background: Anemia is a worldwide problem with serious effects for mothers and their babies. Although efforts have been made to lessen the burden of anemia, it has remained a problem. Moreover, there is a paucity of information regarding the perinatal outcomes of anemia in the study area. Thus this study aimed to assess the perinatal outcomes in anemic pregnant women in eastern Ethiopia. Methods: A facility-based cross-sectional study was conducted among 407 systematically selected pregnant women. Data were collected by interview and entered into EpiData version 3.1 and then exported into SPSS for Windows version 20 for analysis. Bivariate and multivariate analyses were employed to determine the association between independent variables and the outcome variable. Results: Among pregnant women, 61.9% had an adverse perinatal outcome. The most common reported adverse perinatal outcomes were preterm birth, congenital anomalies and stillbirths. Furthermore, variables such as educational status (adjusted odds ratio [AOR] 2.11 [95% confidence interval CI 1.245 to 3.58]), antenatal care follow-up (AOR 2.75 [95% CI 1.47 to 5.18]) and hemoglobin level (AOR 4.1 [95% CI 2.609 to 6.405]) were significantly associated with perinatal outcomes. Conclusions: Nearly three-fourths of anemic pregnant women experienced adverse perinatal outcomes. In general, this study identified that educational status, antenatal follow-up and hemoglobin level were associated with perinatal outcomes among anemic pregnant women. To prevent adverse perinatal outcomes, efforts must be made to ensure that all pregnant women receive antenatal care and have adequate maternal nutritional status.